Bringing Laxmi and Saraswati together: Nano-scientists and academic entrepreneurship in India. (November 2020) - Pandey, Poonam; Pansera, Mario
Abstract: Innovation fuelled by Science & Technology is seen as the panacea for growth, inclusive development and international competitiveness. Aligned with this view, there is a growing interest in the role of academic entrepreneurship in contributing to these goals. A huge emphasis is also given to ready-made, transportable success models of innovation to be replicated into a variety of local contexts. Most of the scholarly literature in this domain focusses on the global north whereas studies on in the global south remain scarce. In this paper, we focus on scientists working in the field of nanotechnology in India. Drawing on semi-structured interviews and document analysis, the paper contributes to shed light on the perceptions of scientists and policy makers about the changing role of Indian universities in the context of global aspirations associated to academic entrepreneurship, and the socio-cultural aspects underpinning such perceptions. Highlights: The paper analyses the socio-cultural underpinning of academic entrepreneurship in India. Data collected through interviews with nano-scientists is analysed using an inductive research approach. Scientists' perceptions of barriers and motivations for academic entrepreneurship in a global south setting are discussed. Most scientists support or pursue academic entrepreneurship for creating social impacts of their research.